System-level efficiency optimization of a linear induction motor drive system - Wei Xu; Dong Hu; Gang Lei; Jianguo Zhu (CES Transactions on Electrical Machines and Systems, 2019)
Linear induction motors are superior to rotary induction motors in direct drive systems because they can generate direct forward thrust force independent of mechanical transmission. However, due to the large air gap and cut-open magnetic circuit, their efficiency and power factor are quite low, which limit their application in high power drive systems. To attempt this challenge, this work presents a system-level optimization method for a single-sided linear induction motor drive system. Not only the motor but also the control system is included in the analysis. A system-level optimization method is employed to gain optimal steady-state and dynamic performances. To validate the effectiveness of the proposed optimization method, experimental results on a linear induction motor drive are presented and discussed.